2019
DOI: 10.14429/djlit.39.3.14065
|View full text |Cite
|
Sign up to set email alerts
|

Research Output of Biological Science during 1901 1945 A Scientometric Analysis

Abstract: A scientometric evaluation of India's scientific productions in the field of biological science during has been performed. The growth rate, authorship pattern, collaboration trend, and prolific researchers (male and female) of biological science literature is investigated. From the result it is found that the mean relative growth rate and duplication time is 0.615 and 1.007 respectively for the period 1901-1945. The calculated results follow the spirit of the 'Price Law' i.e. the coefficient of determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The authors found an average annual growth of 36.84%. Roy (2019) assessed the research scenario in biological science by Indian authors from 1901-1947. The study found that 0.615 is relative mean growth and 1.007 is duplication time.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The authors found an average annual growth of 36.84%. Roy (2019) assessed the research scenario in biological science by Indian authors from 1901-1947. The study found that 0.615 is relative mean growth and 1.007 is duplication time.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Only few authors were found productive in the field of LIS in Nigeria taken under the purview of study. Roy (2019) examined the Lotka’s law with the author productivity data of biological science research indexed in Indian Science Abstract (1935–1939), Biological Abstract and the Zoological Record of the Zoological Society of London (1901–1947). The study confirmed the fitting of Lotka’s law with observed author productivity data.…”
Section: Literature Reviewmentioning
confidence: 99%